HR Roles in Addressing the Challenges of Industry 4.0: Indonesian Employees Cross-Industry Perceptions - Ester Lisa Mulia The; Anthonius Whisnu Perdana Widiputra; Maria Jacinta Arquisola (International Journal of Business Studies, 2020)
In light of rapid changes in technology known as Industry 4.0 (IN4.0), this study aims to examine how Indonesian employees perceive the HRM function is being implemented in their organizations using the Ulrich Multiple Roles of HR model, and whether they believe the HR roles are effective to address the challenges of IN4.0. Cross-industry data was collected from 160 respondents representing five priority industries: food and beverages, automotive, electronics, textiles, and chemicals. Through descriptive and factor analysis, results show that the HR function in Indonesia is still widely administrative in nature, and being an agent of change is the least performed HR role. In addition, the results indicated that the HR roles in Indonesia are changing towards a more strategic direction even though the change is slow. HR practitioners must heed the expectations of employees to ensure there are interventions that can be implemented to prepare human capital for IN4.0. This is the first type of research that examined how Indonesian employees perceive the HR roles in Indonesian industries are being performed, adding to the scant literature on HR roles in an Indonesian context, and addressing the need for relevant studies on the impact of IN4.0 and HR roles.